Sales Forecasting in the Context of Seasonal Activities and Company Sustainable Growth - Ion Stancu; Dumitra Stancu; Dalina Dumitrescu; Andrei Tinca (Amfiteatru Economic Journal, 2015)
The paper presents the use of the "time series model" to forecast the quarterly and yearly sales for a company with busi ness seasonality. These sales forecasts will represent the fundamental basis for estimating the external financing, using the percentage to sales method. Sales growth rates are afterwards analysed in the context of ensuring a sustainable and self-financed growth. We focus on establishing the forecasted fi nancial structure of the external financial requirements both in the context of using th e reinvested profit complemented with credit, maintaining the debt rate constant, and in the context of total internal funding of the company economic growth, from reinvested profit.
Keywords: C53; D24; M11; 330; sales forecasting; quantitative forecasting methods; qualitative forecasting methods; additional capital requirements; sustainable growth